2004
DOI: 10.1167/iovs.03-1105
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Retinal Vascular Endothelium to Infection withToxoplasma gondiiTachyzoites

Abstract: Enhanced susceptibility of retinal vascular endothelium to infection by T. gondii tachyzoites may explain, at least in part, preferential localization of T. gondii to the retina. Susceptibility may relate to preferential binding of tachyzoites to the retinal vascular endothelial surface, relative ease of penetration into the cell, rate of replication within the cell and/or cell response to infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 28 publications
0
23
0
3
Order By: Relevance
“…Replication speed of the parasite seemed to affect its virulence [60] . Smith et al [62] found that retinal vascular endothelium cells have enhanced susceptibility to infection with T. gondii tachyzoites in comparison with aorta (55% more), umbilical vein (33%), and dermal endothelial cells (34% more), and tropism of different pathogens for particular cell types and/or specific tissue sites was a long-recognized biological phenomenon [62] . Free T. gondii tachyzoites had the ability to transmigrate a stimulated human retinal endothelium monolayer [63] .…”
Section: Vascular Endothelial Cells Are Susceptible To Infection Withmentioning
confidence: 99%
“…Replication speed of the parasite seemed to affect its virulence [60] . Smith et al [62] found that retinal vascular endothelium cells have enhanced susceptibility to infection with T. gondii tachyzoites in comparison with aorta (55% more), umbilical vein (33%), and dermal endothelial cells (34% more), and tropism of different pathogens for particular cell types and/or specific tissue sites was a long-recognized biological phenomenon [62] . Free T. gondii tachyzoites had the ability to transmigrate a stimulated human retinal endothelium monolayer [63] .…”
Section: Vascular Endothelial Cells Are Susceptible To Infection Withmentioning
confidence: 99%
“…Fasting increases PEPCK-C production and fatty acid release is restrained due to increased glyceroneogenesis and reesterification in triacylglycerols, which requires glycerol-3-phosphate formation from non-carbohydrate precursors [766]. tachyzoites to the retinal vascular endothelial surface, relative ease of penetration into the cell, rate of replication within the cell and/or cell response to infection, as compared with aortic (55% more), umbilical vein (33%) and dermal (34%) endothelial cells [786]. It appeared that growth of the tachyzoites was approximately 2.8-fold higher in retinal endothelium than in foreskin fibroblasts [786].…”
Section: T Gondii Infectionmentioning
confidence: 99%
“…tachyzoites to the retinal vascular endothelial surface, relative ease of penetration into the cell, rate of replication within the cell and/or cell response to infection, as compared with aortic (55% more), umbilical vein (33%) and dermal (34%) endothelial cells [786]. It appeared that growth of the tachyzoites was approximately 2.8-fold higher in retinal endothelium than in foreskin fibroblasts [786]. Binding of the parasite to host cells is partially mediated by interaction with sulfated glycosaminoglycans (GAGs).…”
Section: T Gondii Infectionmentioning
confidence: 99%
“…They were able to demonstrate significant increase in the migration and proliferation of cultured human choroidal, but not retinal, ECs, in response to exogenous NGF, an effect that appeared to be mediated by phosphorylation of its receptor, TrkA, as well as signaling proteins Src, Akt and MAPK. Work from our laboratory has shown that cultured human retinal EC are preferentially susceptible to infection with T. gondii tachyzoites in comparison to human ECs from extraocular sites, including aortic ECs, human umbilical venous ECs and dermal ECs [39]. The human retinal endothelium is capable of binding tachyzoites in a modified Woodruff-Stamper assay [40], and the relative susceptibility of cultured human retinal ECs to infection reflects an enhanced parasite-host EC binding and penetration, at least in comparison to dermal ECs [41].…”
Section: Ocular Vascular Endothelial Hetero-geneity: Evidence From Inmentioning
confidence: 99%